56th AIAA/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2015
DOI: 10.2514/6.2015-0701
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics and Finite Element Investigation of Polymer Interphase Effects on Effective Stiffness of Wavy Aligned Carbon Nanotube Composites

Abstract: Interphase effects have been studied for their effect on composite properties for many decades, and it is well documented that an interphase can exist in polymer composites comprised of nanofibers as well. We present a first study of interphase effects on the basic elastic response of wavy aligned carbon nanotube (A-CNT) polymer nanocomposties (PNCs). Waviness is characterized by ex situ pre-fabrication imaging of A-CNT forests and used as an input to finite element analyses of the PNCs containing an interphas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It is important to note that the properties in Table 1 However, they can be estimated using methods described elsewhere [11,18,36].…”
Section: Mechanical Deformationmentioning
confidence: 99%
“…It is important to note that the properties in Table 1 However, they can be estimated using methods described elsewhere [11,18,36].…”
Section: Mechanical Deformationmentioning
confidence: 99%
“…67 showed that when the interphase size is very small and the CNTpolymer interfacial strength is 150 MPa, as reported by recent studies, [68][69][70] the assumption of perfect bonding will have a very small impact on the predicted effective modulus of the A-PNCs. A recent study showed that for an interphase thickness of ∼ 1 nm, the reinforcement modulus of the CNTs in the A-PNCs would be diminished by 3% for 0.1 ≤ w ≤ 0.5, 71 which also confirms that interphase effects will have a very weak influence on E pnc (V f ) (from Eq. 2c).…”
Section: Mechanical Modeling and Effective Nanocomposite Modulusmentioning
confidence: 64%
“…It is well-known that interfacial interactions can dominate the mechanical and thermal behavior of composites even at low CNT V f (∼1 vol % as-grown A-CNTs with ∼70 nm Γ values) and particularly as the CNT V f increases, such as for densified 30 vol % A-CNT arrays with ∼6 nm Γ values. ,,, In these cases, the interfacial surface area-to-volume ratio is large (i.e., ∼700× larger for a typical 10-nm-diameter CNT compared to a 7-μm-diameter carbon fiber, both at 60 vol % in a composite), the interphase region can extend 1–100 nm from the CNT surface depending on the polymer, , and Γ is small and on the order of the radius of gyration for polymers (3–30 nm), which therefore has the potential to alter polymer behavior such as polymer chain mobility, crystallinity, glass transition temperature ( T g ), and curing . For example, recent molecular dynamics simulations have predicted a ∼1-nm-thick interphase layer for epoxies surrounding CNTs, as corroborated by experiments, highlighting the utility of both computational and experimental studies to inform composite design via interfacial engineering . It is possible and even likely that the entire polymer matrix can be affected by CNT confinement if only a few nanometers of space exist for the polymer chains to reside between each CNT in a high- V f CNT PNC .…”
Section: Introductionmentioning
confidence: 99%
“…8,11,22,23 In these cases, the interfacial surface area-to-volume ratio is large (i.e., ∼700× larger for a typical 10-nm-diameter CNT compared to a 7-μm-diameter carbon fiber, both at 60 vol % in a composite), the interphase region can extend 1−100 nm from the CNT surface depending on the polymer, 18,24 and Γ is small and on the order of the radius of gyration for polymers (3−30 nm), which therefore has the potential to alter polymer behavior such as polymer chain mobility, crystallinity, glass transition temperature (T g ), and curing. 25 For example, recent molecular dynamics simulations have predicted a ∼1-nm-thick interphase layer for epoxies surrounding CNTs, 24 as corroborated by experiments, 26 highlighting the utility of both computational and experimental studies to inform composite design via interfacial engineering. 18 It is possible and even likely that the entire polymer matrix can be affected by CNT confinement if only a few nanometers of space exist for the polymer chains to reside between each CNT in a high-V f CNT PNC.…”
mentioning
confidence: 99%